2011
DOI: 10.1021/jp1093004
|View full text |Cite
|
Sign up to set email alerts
|

Is the Bisphenol A Biradical Formed in the Pyrolysis of Polycarbonate?

Abstract: An unknown species has been detected in the analysis of the products in a pyrolysis of polycarbonate using Li(+) ion-attachment mass spectrometry (IAMS). The mass spectra exhibited a Li(+) adduct peak at m/z 233 that was tentatively assigned to bisphenol A (BPA) biradical. Experimentally, this assignment was supported by the observation that the production rate increased under an inert nitrogen atmosphere. To further confirm the assignment, the stability of the BPA biradical to intramolecular rearrangement rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…First, bisphenol A biradical could be generated during the degradation of the epoxy resin. Bisphenol A biradical was formed in the pyrolysis of polycarbonate and its kinetic lifetime was of order of hours [30] . It was reasonable to speculate that a simple homolytic cleavage of aromatic ether linkages in the epoxy resin could produce the bisphenol A biradical.…”
Section: Impact Of Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…First, bisphenol A biradical could be generated during the degradation of the epoxy resin. Bisphenol A biradical was formed in the pyrolysis of polycarbonate and its kinetic lifetime was of order of hours [30] . It was reasonable to speculate that a simple homolytic cleavage of aromatic ether linkages in the epoxy resin could produce the bisphenol A biradical.…”
Section: Impact Of Temperaturementioning
confidence: 99%
“…LC-MS further identified that the degradation product has a molecular weight of 226. On the basis that (1) bisphenol A was one of the two components of the epoxy resin and (2) non-aromatic compounds were not measured by an UV detector, an intramolecular rearrangement product of bisphenol A biradical, 4,4'-(cyclopropane-1,1-diyl)diphenol, was assigned to the peak [30] .…”
Section: Introductionmentioning
confidence: 99%
“…DPC was supplied by Asahi Kasei Chemicals. A series of magnesium salts with different counter ions (F 2 , Cl 2 , or ClO 4 2 ) and DBU were purchased from Wako Pure Chemical. THF was refluxed with sodium and benzophenon for longer than 12 h and distilled and then used for the ROP of six-membered cyclic carbonates.…”
Section: Reagentsmentioning
confidence: 99%
“…Aromatic polycarbonates, as exemplified by bisphenol A‐based polycarbonates, are one of widely‐used polymers in various industrial applications because of their well transparency, high thermal stability, and mechanical properties . While, aliphatic polycarbonates feature biocompatibility and degradability, which inspires many scientists to explore the application to carriers of drugs and genes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation